Predicting the potential distribution of Taxus cuspidata in northeastern China based on the ensemble model - Baoliang Chang; Chen Huang; Bingming Chen; Ziwen Wang; Xingyuan He; Wei Chen; Yanqing Huang; Yue Zhang; Shuai Yu (Ecosphere)
Abstract Climate change is poised to exert a significant impact on species distribution in the future, and Taxus cuspidata as an endangered species is no exception. Predicting the potential distribution of T. cuspidata is essential for decision‐makers to develop conservation policies and explicitly implement conservation measures. In this study, a combined model was employed to predict potentially suitable habitats for T. cuspidata based on extant data of T. cuspidata distributions in northeastern China. Our findings suggest that mean diurnal range (bio2) and isothermality (bio3) were identified as dominant factors influencing T. cuspidata distribution. Under future climate scenarios, suitable habitat areas increased only in the SSP126 scenario in the 2070s, declining in all other scenarios. In all climate scenarios, the centroid of suitable habitats ultimately shows a trend in northward movement. Decreases in suitable habitat predominantly occurred in Yanbian Korean Autonomous Prefecture, Baishan city, and Tonghua city. Overall, this study highlights a projected habitat reduction due to climate change. Recommendations entail the strategic establishment of nature reserves and the implementation of initiatives aimed at population replenishment.